2012
DOI: 10.1177/1548051812442968
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Quantitative and Qualitative Types of Change

Abstract: In this research, the authors present theoretical explanations for quantitative and qualitative types of changes to evaluate the malleability of general self-efficacy (GSE) and specific self-efficacy (SSE) measures due to domain-specific training. First, the authors hypothesize that the change in the GSE measure due to sales training is a quantitative mean-difference (alpha) change. Second, they hypothesize that the change in SSE due to sales training is a qualitative (beta or gamma) change. Results of latent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 60 publications
(117 reference statements)
1
8
0
Order By: Relevance
“…In addition, the findings highlight the importance of blended training that offers both in-person and virtual platforms and allows for opportunities for vicarious learning, which is a strong predictor of self-efficacy (Bandura, 1986). These results also align with Mencl et al (2012), who noted that successful performance increases self-efficacy, enhancing the learning and performance of new skills and leading to further efficacy and an increase in confidence.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the findings highlight the importance of blended training that offers both in-person and virtual platforms and allows for opportunities for vicarious learning, which is a strong predictor of self-efficacy (Bandura, 1986). These results also align with Mencl et al (2012), who noted that successful performance increases self-efficacy, enhancing the learning and performance of new skills and leading to further efficacy and an increase in confidence.…”
Section: Discussionsupporting
confidence: 88%
“…Coates and Messman-Moore (2014) found that core beliefs mediated the relation between childhood psychological maltreatment and depression in emerging adult women. On the other hand, experiences shaping core beliefs are not restricted to childhood but may be experienced across the entire life span, and they are also not restricted to attachment but may result from all kinds of need-fulfilling striving (e.g., due to work-related experiences; Mencl et al, 2012; Platts et al, 2002).…”
Section: Trait Greedmentioning
confidence: 99%
“…The competency assessment is designed to measure changes in individual participants' knowledge, attitude, self-efficacy, and use of the 25 Clinical Scholars competencies (see Figure 1) over the course of the 3-year program as participants work to implement solutions to wicked problems in their communities. In this survey, we address four measures: knowledge, attitude, self-efficacy, and use [26][27][28][29][30][31][32]. Each measure is adapted from previously validated items, and are measured on a 7-point Likert-type scale.…”
Section: Competency Assessmentmentioning
confidence: 99%